Acute Hemoptysis and Pulmonary Hemorrhage after Judo as Presentation of Intralobar Sequestration - Kleffner, Tim; Holzer, Matthias; Hülskamp, Georg; Feindt, Peter; Groetzner, Jan (The Thoracic and Cardiovascular Surgeon, 2013)
Intralobar sequestration (ILS) is a rare anomaly that is usually diagnosed with symptoms of cough, expectoration, or recurrent pneumonia in children. We experienced a case of an 11-year-old boy with massive hemoptysis after judo sports. He was admitted to hospital and intubated due to respiratory failure. His chest computed tomography (CT) scan which was performed without contrast agent revealed a large intrapulmonary hematoma or tumor, mimicking traumatic hemothorax. Due to blood loss and circulatory instability, emergency thoracotomy was performed and a massive intralobar hemorrhage due to a ruptured ILS artery was found. After lobectomy including resection of the ILS, the patient was stabilized and extubated. Aspergillus was detected in the resected lobe and postoperatively acute respiratory distress syndrome (ARDS) and invasive aspergillosis occurred and was treated specifically. However, the young patient was discharged home 3 weeks later. In young patients with hemoptysis and intrapulmonary hemorrhage after trauma, the possibility of ruptured ILS should be kept in mind. This report shows that ILS can have a dramatic course of disease, and for this reason a nonurgent resection should be considered in all patients when this diagnosis is made.
Keywords: hemoptysis; trauma; pulmonary sequestration; computed tomography; thoracic surgery; aspergillosis